Empowerment of Communities Through the Production of Functional Sorghum-based Food in Langung Village, West Aceh - Andriani, Dewi; Eka Putri, Nafisah Eka Putri; Eka Putri, Suci; Irawan, Jekki; Putri Arisma, Mawaddah; Agam Syahputra, Rizki; Ulhaq, Riza; Lestari, Rachmatika; Yasrizal, Yasrizal (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: This innovation aims to enhance the skills members and support nutritional improvement efforts to prevent stunting in the area. The program also includes training in packaging and product branding to increase the competitiveness and market in local markets. Contribution: Sorghum is being promoted as an alternative food source due to its nutritional content, which can help regulate blood sugar levels and prevent stunting in the community. Method: The methods used included community education, mentoring, and community development. The stages of the activity consisted of socialization, training on sorghum-based food products, product packaging and branding, data collection, and evaluations. Results: The results of the sorghum flour cookie processing showed that 80% of respondents stated the taste was delicious, and 72% said the eggroll product was delicious. Conclusion: This activity has a positive impact on product diversification for the partners and is expected to be sustainable for community empowerment. Sustainability is supported through mentoring, the development of SOPs, partnerships and community-based business units, as well as the role of local policies in strengthening agriculture.